Features of the environment and its impact on the competitiveness of economic entities Katlabuzka settlement community of Izmail district - Moskaliuk, Serhii (Journal of Danubian Studies and Research, 2025)
The ongoing transformational crises in public life at the end of the 20th and the beginning of the 21st century, the new administrative-territorial reform, the active phase of the Russian-Ukrainian war, and the expectedly complex process of post-war recovery are key factors contributing to current negative developments, as well as drivers for strategic planning to improve the competitiveness of local economic actors. After the war ends, competition for financial and human resources will intensify significantly. Therefore, the Katlabuzka territorial community must already be preparing for post-war recovery to lay the foundation for sustainable development. To address these challenges, it is essential to orient the community's socio-economic-ecological system toward integrated development across all of its subsystems. The main components include: The natural environment – natural resources and conditions, and the nature of human impact on them; Human potential – a modern term increasingly used instead of “population,” including demographic trends, labor resources, skill levels, and the satisfaction of educational, cultural, sports, and other social needs; The economy (anthropogenic pressure) – the structure of the economy, its adaptation to changing natural and climatic conditions, the development of the agro-industrial complex, promotion of craft production, and the increase of added value in local products; Institutional capacity – the competence and effectiveness of public administration bodies, the development of efficient service delivery systems, and a strong local business infrastructure. Taking into account the needs and demands of each of these components in order to develop the community system as a whole will allow for the achievement of the desired outcome – enhancing competitiveness (capacity), building the foundation for sustainable development, and improving the quality of life for the population.